WATER AND GAS ABSORPTION OF POLYTETRAFLUOROETHYLENE AS A PIPELINE - KUANG, ZHI WEN (IRC, 2020)
Polytetrafluoroethylene is a material which exhibits good properties such as high melting point, low coefficient of friction, thermally stable, high electrical resistance, and good chemical inertness. Due to these properties, polytetrafluoroethylene has been widely applied in various fields such as automotive industries, biomedical and pharmaceutical applications, chemical industries, electrical applications, defense application, petrochemical industries, food processing and aerospace technology. Currently, there is limited studies on suitability of polytetrafluoroethylene as a pipeline material for hydrocarbon transportation. This project will focus on study of water and gas absorption characteristics of polytetrafluoroethylene as a pipeline and the effect to weight changes and appearance of polytetrafluoroethylene after immersed and exposed to various mediums and conditions. Water absorption of polytetrafluoroethylene is examined using common medium found causing corrosion of pipeline during hydrocarbons transportation, which are CO2, acetic acid, and sea water. The temperature and pressure for transporting different hydrocarbon types can be vary based on their number of hydrocarbon chain. Normally, hydrocarbon transportation will be conducted with suitable temperature and pressure based on hydrocarbon properties such as wax appearance temperature, pour point temperature and hydrate formatting temperature and pressure. These properties can be obtained from on-site lab test. In this study, water absorption test and gas exposure test are carried out.